Ecological risk assessment of heavy metals (Pb, Cd, Cr, Ni, Zn, Fe) and metalloid (As) in surface sediment of Anzali International Wetland, Iran - Zhaleh Amini; Masoud Hatami-Manesh; Jaber Aazami; Mozhgan Savabieasfahani (Geology, Ecology, and Landscapes, 2024)
This study aimed to assess the metal concentration, mobility, bioavailability, ecological risk, and toxicity in the surface sediment of Anzali International Wetland. Contamination and ecological risk were evaluated using parameters such as Global Contamination Factors (GCF), Risk Assessment Code (RAC), Toxic Unit (TU), sum of Toxic Units (ΣTUs), Toxic Risk Index (TRI), ecological risk (ER), Risk Index (RI), and modified Hazard Quotients (MHQ). Heavy metal mean concentrations (mean ± SD) ranked as follows: Zn (95.46 ± 20.71) > Cr (19.79 ± 2.79) > Ni (18.49 ± 5.23) > Pb (13.97 ± 3.20) > As (6.45 ± 1.87) > Cd (0.90 ± 0.34). Cd exhibited high mobility and bioavailability, while Cr, Pb, Zn, Ni, and As mainly existed in residual fractions, indicating low bioavailability and minimal ecological risk. Ecological risk assessment identified “moderate” to “considerable” risk potential for Cd at specific sites. The Risk Index categorized Anzali sediment as having “low” to “moderate” risk potential (150 < RI < 300). Values of RI, ΣTUs, and MHQ suggested low to moderate risk potential and low toxicity in the sediment. Global Contamination Factor (GCF) values indicated high contamination (12.53 to 79.11). Recommendations include installing effective sewage treatment plants and promoting proper agricultural practices to mitigate metal toxicity in Anzali Wetland and also protect human and environmental health.